A systematic review on digital tools application and language learners’ creativity - Brennen Joseph, Sta Maria; Hafizoah, Kassim; Ruhil Amal, Azmuddin; Murizah, Kassim (Penerbit UMPSA, 2024)
The integration and utilisation of digital tools in language classes should be considered for its influences on student learning, and enhancement of their language skills and creativity. Existing research suggests that digital technologies can assist language learners be more creative, but new research in this area is still scarce. This paper therefore reports a systematic synthesis of journal articles emphasising on the use of digital tools and its influences and relationship with creativity in language classroom. At the final stage of identification, 13 relevant journal articles from an initial sample of 226 were selected for analysis. To provide a comprehensive picture of the current status of research, the journal papers were evaluated. The findings revealed a positive outcome on the use of digital tools on language learners’ creativity. Generally, the findings conclude that research related to digital tools and creativity has dealt with major concerns in the field. Notably, additional research on the impact of digital tools on creativity in language education is recommended. The synthesis will be of interest to both researchers and practitioners in the field of creativity and education, concerning the use of digital tools.